2014
DOI: 10.1016/j.aat.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4% articaine and 0.5% bupivacaine anesthetic efficacy in orthodontic extractions: Prospective, randomized crossover study

Abstract: Articaine seemed to have better potency and efficacy in terms of onset of action and lower pain scores compared to the bupivacaine group. Further studies are required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…However, no statistically significant differences in anesthetic efficacy were recorded between the two solutions. [ 21 22 ] In addition, Ashraf et al . [ 23 ] conducted a double-blind randomized trial on 125 patients to compare the anesthetic success rate of BI injections of articaine and lidocaine when supplemented with an IANB using either 2% lidocaine or 4% articaine.…”
Section: Discussionmentioning
confidence: 99%
“…However, no statistically significant differences in anesthetic efficacy were recorded between the two solutions. [ 21 22 ] In addition, Ashraf et al . [ 23 ] conducted a double-blind randomized trial on 125 patients to compare the anesthetic success rate of BI injections of articaine and lidocaine when supplemented with an IANB using either 2% lidocaine or 4% articaine.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally effective concentration of adrenaline added to bupivacaine is 1 mg/ml. Addition of adrenaline with bupivacaine hydrochloride produces pain relieving effect, decreases the absorption of local anesthetic agent which prolongs the duration of action thereby decreases blood concentration of drug and its toxicity and adverse drug reaction [33,34].…”
Section: Discussionmentioning
confidence: 99%
“… pulpal anaesthesia in the anterior mandible compared with inferior dental block (IDBs) . is suitable for exodontia in adults and children is ideal for implant surgery is suitable for periodontal surgery improved patient comfort. Patients will undoubtedly prefer having full lingual sensation and shorter duration LA anaesthesia after dental treatment …”
Section: Part B: Local Anaesthetic‐related Nerve Injuries – a Modern mentioning
confidence: 99%
“…There has been a resurgence in interest in infiltration anaesthesia in the mandible as a consequence of the introduction of 4% articaine. Recent studies have suggested that infiltration of 4% articaine in the mandibular molar region can obtain anaesthesia of the lower first molar that is as effective as an inferior dental block. Thus, it is ironic that 4% articaine, the drug that has caused such controversy concerning nerve damage, may be helpful in preventing this complication.…”
Section: Should Our La Practice Change?mentioning
confidence: 99%